Bitcoin return dynamics volatility and time series forecasting - Anand, Punit; Sharan, Anand Mohan (International Journal of Financial Studies, 2025)
Bitcoin and other cryptocurrency returns show higher volatility than equity, bond, and other asset classes. Increasingly, researchers rely on machine learning techniques to forecast returns, where different machine learning algorithms reduce the forecasting errors in a high-volatility regime. We show that conventional time series modeling using ARMA and ARMA GARCH run on a rolling basis produces better or comparable forecasting errors than those that machine learning techniques produce. The key to achieving a good forecast is to fit the correct AR and MA orders for each window. When we optimize the correct AR and MA orders for each window using ARMA, we achieve an MAE of 0.024 and an RMSE of 0.037. The RMSE is approximately 11.27% better, and the MAE is 10.7% better compared to those in the literature and is similar to or better than those of the machine learning techniques. The ARMA-GARCH model also has an MAE and an RMSE which are similar to those of ARMA.
Keywords: ARMA; ARMA-GARCH; Econometrics; Economics; Financial economics; MAE; Mathematics; RMSE; Series (stratigraphy); Statistics; Time series; Volatility (finance); bitcoin; dept.fin; time series

US bank lending to small businesses: an analysis of covid-19 and the paycheck protection program - Abugri, Benjamin A.; Osah, Theophilus T. (Journal of Risk and Financial Management, 2025)
This paper examines the characteristics of banks and their lending behavior in relation to Paycheck Protection Program (PPP) loans and commercial and industrial (C&I) loans to small businesses during the COVID-19 pandemic. Our findings show that lenders facing greater risk tended to lend more PPP loans, consistent with the risk-aversion theory. Specifically, banks with a higher loan–deposit ratio, lower overall profitability, poorer loan quality, and higher exposure to risks in business (C&I) loans are characterized by higher PPP loans. C&I loans to all businesses are negatively related to the loan–deposit ratio and loan loss allowance ratio, but are positively linked with the capital ratio. However, we find important differences in C&I lending to small businesses versus large businesses. Furthermore, there is evidence regarding the success of targeting PPP loans towards more productive sectors of the US economy. Using FDIC-defined banks’ lending specializations, we show that banks focused on international lending had a limited role in PPP lending.
Keywords: 2019-20 coronavirus outbreak; Business; COVID-19 pandemic; Coronavirus disease 2019 (COVID-19); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); US banks; Virology; commercial and industrial loans; dept.fin; paycheck protection program; peer-reviewed; risk aversion; small business lending

Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.

Productivity Gaps and Global Systematic Risk Exposure: Pricing Country-Industry Portfolios - Anand, Punit; Balvers, Ronald J. (2020)
Shocks transmitted from productivity leaders to lagging economies are systematic sources of risk. Global technology and knowledge diffusion leads to predictable patterns in productivity dynamics across countries and industries. Technology gaps determine the level of exposure to the systematic productivity shocks. Firms in a country-industry with larger technology gaps relative to the world leader are more dependent on the leader’s innovations compared to their own productivity improvements. They thus have higher loadings on the leader productivity shocks and higher average stock returns. For OECD panel data, a country-industry’s technology gap significantly predicts the stock returns of the country-industry: holding the quintile of country-industry portfolios with the largest gaps and shorting the quintile with the smallest gaps generates annual returns of 9.8% (6.7% after risk adjustment with standard factors). A factor representing the technological productivity gap explains country-industry portfolio returns substantially better than standard factor models. Loadings on leader-country productivity shocks have substantial correlation with technology gaps, and leader productivity shocks are more important for stock returns than idiosyncratic productivity shocks. These findings support that the technology gaps and associated higher average returns are indeed linked to systematic risk.
Keywords: International Equity Returns; OECD Countries; Production-Based Asset Pricing; Productivity Gap; Technology Diffusion; Total Factor Productivity; dept.fin

Ex Ante Predictability of Stock Returns in a Frontier Market - Nguyen, Khoa (Applied Finance Letters, 2022)
This study reports results on the ex ante predictability of stock returns using real-time stock market data in Vietnam, a frontier market, from June 2008 to June 2021. Countries classified as a frontier market are often known for currency manipulation, financial market illiquidity, and political instability. Despite the enormous risk usually posed by these inefficiencies, potential profits are large and achievable for many investors. This study provides evidence on existing a strategy to form out-of-sample long portfolios that generate statistically significant and positive mean monthly returns even in the presence of transaction costs. I also justify the magnitude of these returns by showing that they exceed those of VnIndex and MSCI Vietnam Index. The results reject the hypothesis that the stock prices in Vietnamese market follow random walks, thus oppose the stock market efficiency hypothesis. Evidence found in this study provides a better understanding of informational efficiency in a frontier equity market setting. Specifically, there are several implications on portfolio selection strategies, stock price patterns, and trading behavior bias related to Vietnamese stock market can be drawn from this study.
Keywords: dept.fin; peer-reviewed

External vs. In-House Advising Service: Evidence from the Financial Industry Acquisitions - Huang, Jian; Yu, Han; Zhang, Zhen (Journal of Risk and Financial Management, 2023)
This study analyzes the wealth impact on M&A deals when the acquirers in the financial industry utilize external versus in-house advising services. A quasi-natural observatory setting is applied to investigate the costs and benefits of retaining a financial advisor. Based on agency theory, information asymmetry and conflict of interest both exist in the setting of M&A deals when acquirers use advisory services. We first find that almost 40% of financial acquirers are more likely to use in-house advising services, the frequency of which is significantly higher than that of non-financial acquisitions previously documented. Further, we find that in certain complex deals of greater information asymmetry, the frequency of retaining advisory services in-house is even higher. This finding suggests that for financial acquirers who possess expertise in the M&A market, the concern of conflict of interests (i.e., misaligned incentives) between the acquirers and their advisors are more salient than the concern of information asymmetry. More importantly, using the two-stage regressions method controlling the endogeneity of the choice between in-house versus external advisory services, this study finds that the three-day abnormal returns around the acquisition announcements are 4.5% higher for the acquirers retaining in-house advisory services, 18.7% higher for the corresponding target, and the combined merger gains are 2.2% higher. Overall, our findings provide direct evidence of the agency cost when an external advisor is hired and document the incremental values that the financial acquirers’ in-house advisory services may create.
Keywords: agency costs; dept.fin; external advisors; financial industry; in-house advisors; information asymmetry; peer-reviewed

Ex-ante performance of REIT portfolios - Birz, Gene; Devos, Erik; Dutta, Sandip; Nguyen, Khoa; Tsang, Desmond (Review of Quantitative Finance and Accounting, 2022)
The Real Estate Investment Trust (REIT) market has become an increasingly important vehicle for alternative investment for equity investors. While existing research examining the cross-section of REIT returns usually employs standard risk factors in the in-sample models, it can only show the ex-post performance of REIT portfolios. The goal of our paper is to examine the ex-ante performance of REIT portfolios (i.e., the ability of investors to earn abnormal returns in real time). We employ the out-of-sample methodology of Cooper, Gutierrez, and Marcum (2005), and show that ex-ante performance of REIT portfolios is rather weak. For about half of our 19-year sample over the period of 1999 to 2017, the portfolio performances of REITs chosen ex-ante do not beat the performances of the FTSE-NAREIT or the CRSP Equal-Weighted index. After adjusting for transaction costs, the REIT portfolios significantly further underperform their benchmarks. Overall, our findings suggest that the market is relatively efficient in the REIT sector, and it is difficult for investors to devise trading strategies that improve the ex-ante performance of REIT portfolios, based on standard risk factors.
Keywords: Abnormal returns; Out-of-Sample; Portfolio management; Predictability; REITs; Real estate; dept.fin; peer-reviewed

Emerging market hedge funds: Analysis of security selection and market timing - Dutta, S. (Banking and Finance Review, 2012)
Recent studies have documented that it is only very recently that the Emerging Market Hedge Funds (EMHFs) have started mimicking the performance pattern of regular Hedge Funds. These findings therefore motivate us to analyze the market timing and security selection skills of EMHF managers. Rolling regression technique is employed to analyze the above mentioned issues on a time-varying dimension. The rolling market timing regression results suggest that the EMHF managers do not exhibit consistently superior security selection or market timing skills even in an up-market scenario. The static market timing models however, indicate significant outperformance due to superior security selection and significant underperformance due to perverse market timing for the EMHFs in general. Multifactor asset class regressions, using fund-level data, reaffirm the notion that the EMHFs mimic the performance pattern reported for mutual funds in the mutual fund literature. © 2012, Banking and Finance Review.
Keywords: Emerging market; Hedge Funds; Security selection; dept.fin; ⛔ No DOI found

Measuring systematic risk from managerial organization capital - Yildirim, Alev; Allen, Linda (Journal of Business Finance & Accounting, 2021)
Keywords: dept.fin; peer-reviewed

A coronavirus outbreak and sector stock returns: a tale from the first ten weeks of 2020 - Nguyen, Khoa Huu (Applied Economics Letters, 2021)
This paper examines early impacts of the COVID-19 outbreak on stock returns of 11 sectors using the firm-level stock price data from 10 countries. Results show that investors across sectors and countries respond differently during the outbreak. Communication Services, Consumer Staples, Health Care, Information Technology, and Utilities sectors consistently perform relatively well, compared to other sectors, in all countries except Italy, Japan and U.S. Conversely, Energy sector suffers greatest abnormal negative returns, among all sectors, in countries including Canada, Italy, U.K. and U.S. Furthermore, Japan and U.S. have highest numbers of abnormally and negatively affected sectors. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.fin; peer-reviewed

Economic forecasts, anchoring bias, and stock returns - Birz, Gene; Dutta, Sandip; Yu, Han (Financial Management, 2021)
By utilizing survey forecasts of macroeconomic statistics, we find that market participants’ expectations are not rational as they exhibit an anchoring bias. The forecasts systematically underpredict macroeconomic statistics and the forecast errors are predicted by past macroeconomic announcements. Most importantly, we find that the stock market does not see through this bias, that is, we find statistically significant stock price effects of “anticipated” components of macroeconomic announcements. Investors overweight the importance of historical information and do not make sufficient adjustments after the arrival of new information. © 2021 Financial Management Association International
Keywords: dept.fin; peer-reviewed

Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
Keywords: dept.eco; dept.fin; peer-reviewed

Short selling prior to going concern disclosures - Huang, Jian; Wang, Lei; Yu, Han; Zhang, Zhen (Accounting and Business Research, 2020)
We provide insights into how the market processes going concern audit opinions based on the trading of some well-documented sophisticated investors–short sellers. We find that abnormal short selling increases significantly upon impending going concern disclosures. While prior literature attributed much of short selling around some corporate events to private information, we find evidence that pre-going-concern announcement short selling reflects both privately informed trading and processing of public information by short sellers. Further, a negative relation between pre-announcement short selling and post-announcement short-term stock returns exists for stocks with less short sale constraints. We also find moderate evidence associating short selling with subsequent bankruptcy to some extent. Overall, these results suggest that short sellers front run going concern announcements based on private information and fundamentals, although trading constraints prevent them fully impounding the severity of negative information in the short run, providing a partial explanation for the long-run price drift post-going concern. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.fin; peer-reviewed

The effect of political risk on shareholder value and the mitigating role of corporate social responsibility (CSR) - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Sarajoti, Pattarake; Singh, Manohar (Managerial Finance, 2020)
Purpose: The study investigates the effect of political risk on shareholder value, using an event study and a novel measure of firm-level political risk recently developed by Hassan et al. (2017). In addition, the authors explore how corporate social responsibility (CSR) influences the effect of political risk on shareholder wealth. Design/methodology/approach: The authors exploit the guilty plea of Jack Abramoff, a well-known lobbyist, on January 3, 2006, as an exogenous shock that made lobbying less effective and less useful in the future, depriving firms of an important tool to reduce political exposure. Findings: The results show that the market reactions are significantly more negative for firms with more political exposure. Additional analysis corroborates the results, including propensity score matching, instrumental-variable analysis and Oster's (2019) method for testing coefficient stability. Finally, the authors note that the adverse effect of political risk on shareholder value is substantially mitigated for firms with strong social responsibility, consistent with the risk mitigation hypothesis. Originality/value: This study is the first to explore the effect of political risk on shareholder value using a novel measure. Furthermore, it is also the first to show that CSR alleviates the cost of political risk to shareholders. © 2020, Emerald Publishing Limited.
Keywords: CSR; Corporate social responsibility; Event study; Firm risk; G34; M14; Political risk; Shareholder wealth; dept.fin; dept.grad; peer-reviewed

Monetary policy, composite leading economic indicators and predicting the 2001 recession - Mostaghimi, M (Journal of Forecasting, 2004)
On 26 November 2001, the National Bureau of Economic Research announced that the US economy had officially entered into a recession in March 2001. This decision was a surprise and did not end all the conflicting opinions expressed by economists. This matter was finally settled in July 2002 after a revision to the 2001 real gross domestic product showed negative growth rates for its first three quarters. A series of political and economic events in the years 2000-01 have increased the amount of uncertainty in the state of the economy, which in turn has resulted in the production of less reliable economic indicators and forecasts. This paper evaluates the performance of two very reliable methodologies for predicting a downturn in the US economy using composite leading economic indicators (CLI) for the years 2000-01. It explores the impact of the monetary policy on CLI and on the overall economy and shows how the gradualness and uncertainty of this impact on the overall economy have affected the forecasts of these methodologies. It suggests that the overexposure of the CLI to the monetary policy tools and a strong, but less effective, expansionary money policy have been the major factors in deteriorating the predictions of these methodologies. To improve these forecasts, it has explored the inclusion of the CLI diffusion index as a prior in the Bayesian methodology. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Composite leading indicators (CLI); Composite leading indicators diffusion index; Diffusion index; Geochronology; Industrial economics; Information theory; Monetary policy; Predicting recessions; Probability; Public policy; Quality control; Set theory; Statistical methods; US economy; Us economy; dept.eco; dept.fin

Orange county bankruptcy: financial contagion in the municipal bond and bank equity markets - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Financial Review, 2004)
We examine the spillover wealth effects of the Orange County, California bankruptcy announcement in December 1994 on municipal bonds, municipal bond funds, and bank stocks. This bankruptcy is prominent because of unprecedented losses and because it was caused by a highly leveraged derivatives strategy rather than a shortage of tax revenues and excess spending. We find contagion in the bond market with significantly negative abnormal returns for municipal bond funds without direct exposure to Orange County and for non-Orange County municipal bonds. In addition, our findings suggest the contagion spills over to the common stocks of investment and commercial banks that deal in or use derivatives; however, the equities of banks unexposed to derivatives are not affected. © 2004 Blackwell Publishing Ltd.
Keywords: Bank equity; Contagion; Derivatives; Fixed income; G2/H3/K2; Municipal financing; dept.eco; dept.fin

Currency substitution: evidence from latin america - Prock, Jerry; Soydemir, Gokce; Abugri, Benjamin A (Journal of Policy Modeling, 2003)
Currency substitution represents a shift from domestic currency to foreign currency and is often related to times of high and variable inflation. In this paper, we investigate the extent of currency substitution in Argentina, Brazil and Mexico using a vector error correction (VEC) model. We empirically test this hypothesis by introducing artificial shocks to the system of equations and find that M1 response to a one standard deviation increase in that country's interest rate is negative and significant for Argentina and Brazil but not for Mexico. An artificially introduced one standard deviation increase in nominal exchange rate results in a statistically significant increase in M1 in Argentina and Brazil but again not for Mexico. Based on the patterns of the impulse response functions (IRFs) and the magnitude of the coefficients, we conclude that currency substitution occurs to a greater extent in Argentina and Brazil than Mexico. This is reflective of the implementation of relatively more credible macroeconomic policies in Mexico after the December 1994 crisis. Thus from a policymaking perspective, it is important to consider that the greater the degree of currency substitution, the more sensitive a country's monetary aggregates are to sudden movements in exchange rates, productivity and interest rates. (C) 2003 Society for Policy Modeling. Published by Elsevier Science Inc. All rights reserved.
Keywords: Currency; Latin America; Substitution; VEC; dept.eco; dept.fin

In-class simulations of the iterated prisoner's dilemma game - Bodo, Peter (Journal of Economic Education, 2002)
The author developed a simple computer program for the in-class simulation of the repeated prisoner's dilemma game with student-designed strategies. He describes the basic features of the software and presents two examples for the use of the program in teaching the problems of cooperation among profit-maximizing agents.
Keywords: Computer simulation; Experiments; Prisoner's dilemma; Repeated games; dept.eco; dept.fin

Exchange rate adjustment in partially liberalized economy - Grubacic, Sanja (Economics of Planning, 2002)
This paper develops a model of exchange rate determination in partially liberalized post-socialist economy that operates under soft budget constraints in nontradable sectors. The model captures the factors that determine the evolution of a country's external balance during the initial phase of economic liberalization. Three types of disturbances are the center of analysis: liberalization of trade and foreign exchange regime, devaluation, and price liberalization. We show that the real exchange rate appreciation may either improve or worsen the trade balance depending on the sources of this appreciation. Thus, we argue that the real exchange rate cannot reflect true country's competitiveness unless all sectors are equally exposed to hard budget constraints. The model implications are further analyzed through the empirical evidence on the relationship between the real exchange rate and trade balance in three selected East European countries.
Keywords: Europe; Exchange rate; External balance; Liberalization; Post-socialist economy; Soft budget constraint; balance of trade; competitiveness; dept.eco; dept.fin; exchange rate; external balance; liberalization; post-socialist economy; real exchange rate; soft budget constraint

Information collection strategic design in experts-assisted decision making paradigm - Mostaghimi, Mehdi (Group Decision and Negotiation, 2001)
In an experts-assisted decision making paradigm, the information collection design becomes a strategic variable under a weak assumption that the final decision is dependent on the design used to collect information as well. As a result, the same information of the experts and the decision maker about the problem can potentially produce different final decisions for different information collection designs. The implication is that a decision maker can strategically select a design which serves his/her objective. This paper uses a Bayesian estimation methodology for combining experts' information with the decision maker's prior. An information collection process is designed by setting constraints on this model. Several designs are developed here using such controlled factors as a one-stage versus a two-stage decision process, experts' rank ordering, and group versus individual lobbying/consultation. An example is provided to illustrate the applicability of the concept. It is shown that the information produced in the process of producing a decision can also give insights into the impacts of the decision maker and the experts on the decision.
Keywords: Bayesian method; Experts-assisted decision making; Information theory; Reaching a consensus; dept.eco; dept.fin; experts-assisted decision making; information theory; reaching a consensus

Emerging market hedge funds: Do they perform like regular hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2009)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period show that EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: Emerging market hedge funds; Hegde funds; Modified Sharpe Ratio; Portfolio performance measures; Risk-adjusted returns; dept.fin

Are we overestimating REIT idiosyncratic risk? Analysis of pricing effects and persistence - Abugri, Benjamin A.; Dutta, Sandip (International Review of Economics & Finance, 2014)
This study uses a multifactor REIT-specific model to estimate and compare REIT idiosyncratic volatility vis-A-vis the same from the Fama-French three-factor model. Estimates of conditional idiosyncratic volatility and conditional betas obtained from a multifactor REIT-returns model and a bivariate EGARCH model respectively are found to be positively and significantly related with REIT returns. Consistent with Merton's (1987) predictions, we observe that larger REITs post higher average returns when idiosyncratic risk is introduced in cross-sectional regressions. Persistence of past market-risk does not appear to be short-lived and seems to have a lasting impact on future idiosyncratic volatility. We also observe mild evidence of persistence of past idiosyncratic risk, albeit short-lived, thereby suggesting that past idiosyncratic risk has a short-term impact on future idiosyncratic risk. Published by Elsevier Inc.
Keywords: Conditional betas; Idiosyncratic risk; REITs; dept.fin

Testing trade-off and pecking order models of capital structure: does legal system matter? - Cotei, Carmen; Farhat, Joseph B; Abugri, Benjamin A (Managerial Finance, 2011)
Purpose – This paper aims to examine the link between financing patterns, information asymmetry and legal traditions in 37 countries during the 1990-2004 period. Design/methodology/approach – The analysis is based on three theories: the trade-off theory, pecking order hypothesis and market timing hypothesis. The authors test the predictions of these theories/hypotheses using regression analysis. The econometric method used is panel data with firm and country fixed effects. The authors develop a modified pecking order model which controls for short- and long-term debt level changes and simultaneously test the predictions of all theories. Findings – Consistent with studies for US firms, the results show that firms across all countries adjust toward the target leverage, but with significantly different rate. The long-term debt contribution in the rate of adjustment is 64 percent in common law countries and 51 percent in civil law countries. The ability of the model to explain changes in leverage ratios is higher in common law countries. The authors find support for market timing hypothesis but no support for pecking order of financing. These results support their conjecture that stronger investor protection, higher transparency and well-developed financial markets in common law countries reduce the cost of recapitalization. Research limitations/implications – The limitation of this study comes from lack of data availability to measure contract enforcement, transparency, and corporate governance variables. Future research can incorporate these variables to explain the differences in capital structure decisions across countries with different legal systems. Practical implications – The findings show that firms' capital structure decisions are not only a function of their own characteristics but also the result of legal and financial market development in which they operate. Originality/value – This is the first study that sheds light about rate of adjustment to optimal capital structure and pecking order of financing in 37 countries with different legal traditions and financial market developments. The authors are not aware of any other study that uses a modified pecking order model in an international context. © 2011, © Emerald Group Publishing Limited.
Keywords: Capital; Financial development; International capital structure; Legal systems; Pecking order theory; Trade-off theory; dept.fin; peer-reviewed

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

The effect of relationship banking on firm efficiency and default risk - Yildirim, Alev (Journal of Corporate Finance, 2020)
Does relationship bank oversight reduce firm default risk and improve firm operational efficiency? I find that a new loan from a relationship bank reduces the default probability and increases the efficiency of a borrowing firm, benefiting both banks and borrowers. Moreover, inefficient and less creditworthy firms experience the highest reductions in their default risks and improvements in their efficiencies in the years following new relationship bank loans. Further, these benefits are disrupted when the relationship bank is acquired.
Keywords: Data envelopment analysis; Default risk; Firm efficiency; Relationship banking; Stochastic frontier analysis; Total factor productivity; dept.fin; peer-reviewed

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Cohabitation before marriage: Do prior alliances enhance post-merger performance? - He, Zhaozhao; Yu, Han; Du, Lijing (Review of Quantitative Finance and Accounting, 2020)
We investigate the impact of prior alliance relationships on subsequent mergers between partner firms. We argue that an acquirer’s prior alliance experience with the target reduces information asymmetry, which helps improve acquisition performance. Alternatively, agency problems arising from familiarity may lead to inefficient decision making. Examining mergers between 1986 and 2014, we find evidence that prior alliance collaboration is positively associated with the acquirer’s long-term profitability and growth. This positive effect is more pronounced when target-specific learning and experience are more crucial to merger success, such as targets in knowledge-intensive or organizational-capital-intensive industries as well as cross-industry mergers. However, we cannot formally rule out the possibility that our results are partly driven by the small size of our sample.
Keywords: D80; G34; Information asymmetry; L14; L24; Learning and resources sharing; Mergers and acquisitions; O30; O32; Post-merger performance; Strategic alliance; dept.fin; peer-reviewed

The intra-industry effects of proxy contests - Chen, Fang; Huang, Jian; Yu, Han (Journal of Economics and Finance, 2020)
In this study, we examine the intra-industry effect of proxy contests. Proxy contests convey the information of common industrial risks or expected competitive relationship change. We find significant negative abnormal returns in the group of competitors of target firms with negative abnormal returns, and such negative abnormal returns become larger for similar-size competitors. In contrast, there are no significant abnormal returns for competitors of target firms with positive abnormal returns. These findings are consistent with the information-based theory but not the competitive theory. © 2019, Academy of Economics and Finance.
Keywords: Competitive effect; Information-based effect; Intra-industry effect; Proxy contest; dept.eco; dept.fin; peer-reviewed

CEO characteristics, firm performance, and corporate political contributions - Subrahmanyam, Vijaya; Singh, Manohar; Pennathur, Anita K. (Review of Financial Economics, 2020)
We investigate if CEO characteristics determine the choice of Political Action Committee (PAC) contributions by firms and if such participation leads to better firm performance. Using a unique, hand-collected database, we also focus on the identity of the politicians receiving PAC contributions to examine the impact of the value-relevance of such contributions. Examining data on corporate contributions made to candidates seeking federal office during the 2002, 2004, and 2006 election cycles, we find that CEO dominance and interest alignment influence strategic choices of firms with regards to establishing PACs. Our analysis of value-relevant contributions shows that firms prefer to donate to politicians representing the state of a firm's headquarters, validating the truth to the adage that all politics is local. However, these targeted political contributions do not have a discernible impact on firm performance.
Keywords: CEO characteristics; CEO dominance; agency theory; corporate political contributions; dept.fin; dept.grad; firm performance; peer-reviewed

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
Keywords: dept.fin

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Institutional ownership and the spillover effects of shareholder activism - Jory, Surendranath; Ngo, Thanh; Nguyen, Khoa Huu (International Journal of Corporate Governance, 2017)
Keywords: dept.fin